COST PROBLEMS ENCOUNTERED IN CPA EXAMINATIONS. - Greene, Howard F. (The Accounting Review, 1946)
Abstract From June, 1917 to November, 1945, in semiannual examinations, the American Institute of Accountants submitted to candidates a total of 724 problems and questions on Accounting Theory and Practice. It is of interest to cost accountants to note that of the 724 problems and questions presented by the Institute 88, or 12.15 per cent of the total, were based on cost accounting or the related subject of inventory valuations, 34 of the 88 being related to inventories. This represents the greatest number of problems based on any one subject. Consolidated financial statements provided the basis for 55 problems and questions, Accounting for Mergers and Reorganizations was the subject of 32 and 32 more were concerned with Municipal Accounting. The obvious inference is that the American Institute Board of Examiners considers the subject of cost accounting to be of in creasing importance. Cost problems encountered in American Institute examinations cover both job order and process cost systems.